Light Rail Transit Systems : 61 Lessons in Sustainable Urban Development - Bijl, Rob van der; Oort, Niels van, 1978-; Bukman, Bert, 1960- (Elsevier, 2018)
"Light Rail Transit Systems: 61 Lessons in Sustainable Urban Development shows how to design and operate light rail to maximize its social benefits. Readers will learn how to understand the value of light rail and tactics on its effective integration into communities. It uses strong supporting evidence and theory drawn from the author's team and their extensive experience in developing new light rail systems. The book uses numerous case studies to demonstrate how key concepts can bridge the geographic limitations inherent in many transit-related discussions. In addition, users will learn how to develop important relationships with local decision-makers and communities. Presents applied research by experienced practitioners and academic researchersDraws on more than 50 cases from Europe, the Middle East, the UK and USIncorporates five themes on why it's important to invest in light rail, including effective mobility, and for an efficient city, economy, environment and equityIncludes a checklist for planning public transport projects"--